Nitrogen removal capability and mechanism of a novel low-temperature-tolerant simultaneous nitrification-denitrification bacterium Acinetobacter kyonggiensis AKD4 - Mao, Jiwei; Zhao, Ruojin; Li, Yiyi; Qin, Wenpan; Wu, Shengchun; Xu, Weiping; Jin, Peng; Zheng, Zhanwang (Frontiers in Microbiology, 2024)
A low-temperature-tolerant simultaneous nitrification-denitrification bacterial strain of Acinetobacter kyonggiensis (AKD4) was identified. It showed high efficiency in total nitrogen (TN) removal (92.45% at 10°C and 87.51% at 30°C), indicating its excellent low-temperature tolerance. Transcriptomic analysis revealed possible metabolic mechanisms under low-temperature stress. Genes involved in cell growth, including ATP synthase (atpADGH), amino acid (glyA, dctA, and ilvE), and TCA cycle metabolism (gltA, fumC, and mdh) were remarkably upregulated from 1.05–3.44-fold at 10°C, suggesting that their actions enhance survivability at low temperatures. The expression levels of genes associated with nitrogen assimilation (glnAE, gltBD, and gdhA), nitrogen metabolism regulation (ntrC, glnB, and glnD), and denitrification processes (napA) were increased from 1.01–4.38-fold at 10°C, which might have contributed to the bacterium’s highly efficient nitrogen removal performance at low temperatures. Overall, this study offers valuable insights into transcriptome, and enhances the comprehension of the low-temperature-tolerant mechanism of simultaneous nitrification and denitrification processes.